DIFFERENTIAL ITEM FUNCTIONING (KEBERBEDAAN FUNGSI BUTIR) - Muh. Ilyas Ismail (Lembaga Pendidikan dan Tenaga Kependidikan (Center for Teacher Training) Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar in collaboration with Lecturer Consortium of Tarbiyah and Teacher Training, 2017)
This paper theoretically deals some aspects related to Differential Item Functioning (DIF), consisting of Test and Test Bias. The purpose of this is to describe the importance of understanding Different Item Functioning or to discuss its existence. Based on the theoretical connotation of DIF, it can be inferred that DIF may be used to make sure whether or not a bias item of a test exists. For example, a test item shows the existence of DIF when the tested from different group having the same ability do not have the same opportunity to answer the item correctly. Therefore, understanding the DIF, a teacher may avoid item bias on a test to exist.